THE STUDY OF PHYSICAL FITNESS FOR THE STUDENTS OF MENTAL RETARDATION IN BENGKULU - Feby Elra Perdima (Journal Physical Education, Health and Recreation, 2019)
This study aimed to determine the level of physical fitness of mental retarded students in Special School of Bengkulu by using the TKJI physical fitness test. This method was a quantitative descriptive method of development from surveys with measurement tests. To develop the physical fitness of test norms for normal students and to be used as test norms as a reference for students having special needs, especially for mentally retarded students in order to see the level of physical fitness. Samples from this study amounted to 25 people through a purposive sampling technique. The results showed the level of mental retardation in Special School of Bengkulu, namely 1 person or (4%) was in the category of Very Good. 3 people or (12%) were in the Good category. 6 people or (24%) were in the Medium category. 6 people or (24%) were in the category of Less. 9 people or (36%) were in the category of Very Less. Therefore, to improve the physical fitness, it was necessary to improve the principle of practice, namely the process of change in a better direction, including improving physical quality, body functional abilities and psychological activity of a person. The higher the physical activity was conducted every day, the better the level of physical fitness was. The better was in the process of growth and development of children, not only the task of the parents but the task of the school as well. Physical education teachers had a very important role in helping students to achieve physical fitness. The teachers could give by providing physical fitness lesson and also exercises for physical integrity for students.